Entangling voluntarism, leisure time and political work: the governmentalities of neighbourhood planning in England. Issue 5 (2nd September 2020) - Parker, Gavin; Dobson, Mark; Lynn, Tessa; Salter, Kat
ABSTRACT: Neighbourhood planning was the first volunteer-led statutory planning tool to be created in the UK. Whilst it has provoked debate and critique covering numerous practical and theoretical aspects, little attention has been paid to the actual experience and motives of the volunteers who spend their leisure time by volunteering to prepare a plan. Given the range of leisure activities that have been shaped in the context of a neo-liberalised policy environment, we add to longstanding debates concerning the political nature of leisure and how neo-liberal policies require, and exploit, volunteer time and input while claiming to offer forms of empowerment. Qualitative data derived from neighbourhood plan volunteers is presented here to highlight the political work of neighbourhood planning, thus responding to calls to extend the analysis of the political in and through leisure. It is argued that neighbourhood planning pushes the boundaries of what can be legitimately asked of volunteers and expected in terms of delivering policy outcomes.